A fair day's pay for a fair day's work: Optimal tax design as redistributional arbitrage - Christian Hellwig; Nicolas Werquin (Federal Reserve Bank of Chicago, 2022)
We study optimal tax design based on the idea that policy-makers face trade-offs between multiple margins of redistribution. Within a Mirrleesian economy with earnings, consumption and retirement savings, we derive a novel formula for optimal income and savings distortions based on redistributional arbitrage. We establish a sufficient statistics representation of the labor income and capital tax rates on top income earners in dynamic environments, which relies on the observed distributions of both income and consumption. Because consumption has a thinner Pareto tail than income, our quantitative results suggest that it is optimal to shift a substantial fraction of the top earners' tax burden from income to savings.
Keywords: 330; capital taxation; income taxation; consumption inequality; Personal Income; Wealth; and Their Distributions; Taxation and Subsidies: Efficiency; Optimal Taxation; Optimale Besteuerung; Einkommensteuer; Sparen; Besteuerungsverfahren; Umverteilung; Theorie